FACTOR ANALYSIS THAT FORMS EXPECTATION OF GUEST HOUSE GUEST EXPERIENCE - Aprillea, Renava; Kusumah, Ahmad Hudaiby Galih; Wirakusuma, Reiza Miftah (Journal of Indonesian Tourism, Hospitality and Recreation)
ABSTRACTThe expectation of Guest House guest experience is the expectation of the guest perspective on what the Guest House will occupy. If the manager can fulfill the guest’s expectation, it can grow the guest’s loyalty and allows being repeater guest. The purpose of this study is to determine what are the factors that forms expectations of Guest House guest experience. This research uses quantitative method with factor analysis. In this study shows that there are four factors forming expectations of Guest House guest experience, spesifically on the youth travellers.Keywords: Factor Analysis, Customer’s Expectation, Experienc, Guest House.